The nexus between labor diversity and firm's innovation - Pierpaolo Parrotta; Dario Pozzoli; Mariola Pytlikova (Institute for the Study of Labor (IZA), 2012)
In this paper we investigate the nexus between firm labor diversity and innovation using a linked employer-employee data from Denmark. Specifically, exploiting information retrieved from this comprehensive database and implementing proper instrumental variable strategies, we are able to identify the contribution of workers' diversity in cultural background, education and demographic characteristics to valuable firm's innovation activity. The latter is measured by: (1) the firm's propensity to apply for a patent, (2) the number of patent applications (intensive margin) and (3) the firm's ability to patent in different technological areas (extensive margin). We find that ethnic diversity plays an important role in propelling firm's innovation outcomes.
Keywords: J15; J16; J24; J61; J82; O32; 330; labor diversity; ethnic diversity; patenting activity; extensive and intensive margins; Diversity Management; Humankapital; Innovation; Patent; Schätzung; Dänemark